Free Zone Scientology and Other Movement Milieus: A Preliminary Characterization - James R. Lewis (Temenos, 2014)
Free Zone refers to the subculture constituted by people and organizations that adhere to the beliefs and practices of Scientology but who do so outside of – and without the sanction of – the Church of Scientology. The analysis in the present article uses the Free Zone plus a selection of comparable subcultures associated with other religious groups as case studies to explore the nature and structure of movement milieus. The notion of a movement milieu is derived from Colin Campbell’s influential formulation, though certain significant features of movement milieus serve to distinguish them from – and to make them more than simply subsets of – the cultic milieu.